Pharmacological and psychosocial interventions for night eating syndrome in adults - dos Santos, Lucas Ribeiro; Duarte, Márcio Luís; Trevisani, Virgínia Fernandes Moça; Peccin, Maria Stella; Melnik, Tamara (Frontiers in Psychiatry, 2025)
BackgroundPathological dietary patterns are influenced by various interacting factors, including psychoactive drugs, psychological and biological conditions, and environmental determinants, and are frequently associated with failure in conventional weight loss treatments, especially in obese individuals. Night eating syndrome (NES) is characterized by excessive food consumption at night, often linked to disrupted circadian rhythms and psychosocial triggers.MethodsThis review evaluated pharmacological and psychosocial interventions for NES in adults. Randomized controlled trials (RCTs) comparing psychological or pharmacological interventions versus control groups were included. Primary outcomes were symptom improvement (reduced nighttime eating/awakenings) and weight loss. Secondary outcomes included changes in quality of life, psychiatric comorbidities, sleep quality, interpersonal functioning, and patient satisfaction. We conducted a systematic search in CENTRAL, MEDLINE, EMBASE, Psych INFO, LILACS, ClinicalTrials.gov, and the WHO’s International Clinical Trials Registry Platform.ResultsA total of 5 RCTs were included. Due to heterogeneity in interventions, a meta-analysis was not feasible, and results were presented narratively. Pharmacological interventions trials (Sertraline, Escitalopram, Agomelatine) showed mixed results in reducing NES symptoms, with Sertraline demonstrating the most significant improvements. Psychosocial interventions, including progressive muscle relaxation and education, also showed some benefits, particularly in reducing evening food intake and improving morning hunger. Weight loss outcomes were variable, with some trials showing modest weight loss in intervention groups.ConclusionBoth pharmacological and psychosocial interventions may provide potential benefits in treating NES. Sertraline shows promise in reducing symptoms and improving quality of life, while psychosocial interventions, particularly progressive muscle relaxation, can modify eating behaviors. However, the heterogeneity of interventions and limited number of studies and subjects included determined a downgraded level of recommendation in GRADE for all outcomes to LOW, suggesting gaps and the need for further research to establish optimal treatment strategies for NES.